2008
DOI: 10.1016/j.yexcr.2008.01.016
|View full text |Cite
|
Sign up to set email alerts
|

RhoA/ROCK-mediated switching between Cdc42- and Rac1-dependent protrusion in MTLn3 carcinoma cells

Abstract: Rho GTPases are versatile regulators of cell shape that act on the actin cytoskeleton. Studies using Rho GTPase mutants have shown that, in some cells, Rac1 and Cdc42 regulate the formation of lamellipodia and filopodia, respectively at the leading edge, whereas RhoA mediates contraction at the rear of moving cells. However, recent reports have described a zone of RhoA/ROCK activation at the front of cells undergoing motility. In this study, we use a FRET-based RhoA biosensor to show that RhoA activation local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
78
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 50 publications
10
78
0
Order By: Relevance
“…14 However, studies examining where Rho GTPases are active in migrating cells demonstrated RhoA activity at the front as well as at the back of a variety of cell types migrating on rigid surfaces. [15][16][17][18] Our work shows for the first time that RhoA is active at the front of T cells under physiological conditions, migrating on and through the pliable EC surface.…”
Section: Rhoa Signaling At the Leading Edge Of Migrating T Cellsmentioning
confidence: 71%
See 1 more Smart Citation
“…14 However, studies examining where Rho GTPases are active in migrating cells demonstrated RhoA activity at the front as well as at the back of a variety of cell types migrating on rigid surfaces. [15][16][17][18] Our work shows for the first time that RhoA is active at the front of T cells under physiological conditions, migrating on and through the pliable EC surface.…”
Section: Rhoa Signaling At the Leading Edge Of Migrating T Cellsmentioning
confidence: 71%
“…For example, RhoA/ ROCK signaling suppresses Rac signaling at the leading edge of EGF-stimulated carcinoma cells, and inhibition of ROCK increased protrusion but reduced migration. 18 Additionally, ROCK/p-MLC is implicated in protrusive force generation at the leading edge of sarcoma cells. 24 ROCKs may drive retraction events to allow cells to reorient their direction of migration.…”
Section: A Possible Role For Rhoa In Integrin Clustersmentioning
confidence: 99%
“…This paper also shows that RhoA should be activated at the leading edge of astrocytoma cells, as previously established for breast cancer cells (El-Sibai et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…Even though protrusion is unaffected, the absence of focal adhesions leads to an ineffective protrusion with not enough traction force on the ECM for the cells to move forward (Gupton, & Waterman-Storer, 2006). In this system and in other systems (El-Sibai et al, 2008), we have shown that defective adhesions due to inhibition of Rac or RhoA, though they do not affect protrusion, inhibit cell motility. Hence, as we describe a need to inhibit RhoA at the tail of cells, we also confirm the newly described role of RhoA at the leading edge of cancer cells undergoing movement, contrary to the canonical distribution of RhoA activation ( Figure 7).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation